Next‐generation sequencing‐defined minimal residual disease before stem cell transplantation predicts acute myeloid leukemia relapse - Press, Richard D.; Eickelberg, Garrett; Froman, Allison; Yang, Fei; Stentz, Alex; Flatley, Ellen M.; Fan, Guang; Lim, Jeong Y.; Meyers, Gabrielle; Maziarz, Richard T.; Cook, Rachel J. (American journal of hematology, 2019)
In acute myeloid leukemia (AML), the assessment of post‐treatment minimal residual disease (MRD) may inform a more effective management approach. We investigated the prognostic utility of next‐generation sequencing (NGS)‐based MRD detection undertaken before hematopoietic stem cell transplantation (HSCT). Forty‐two AML subjects underwent serial disease monitoring both by standard methods, and a targeted 42‐gene NGS assay, able to detect leukemia‐specific mutant alleles (with >0.5% VAF) (mean 5.1 samples per subject). The prognostic relevance of any persisting diagnostic mutation before transplant (≤27 days) was assessed during 22.1 months (median) of post‐transplant follow‐up. The sensitivity of the NGS assay (27 MRD‐positive subjects) exceeded that of the non‐molecular methods (morphology, FISH, and flow cytometry) (11 positive subjects). Only one of the 13 subjects who relapsed after HSCT was NGS MRD‐negative (92% assay sensitivity). The cumulative incidence of post‐transplant leukemic relapse was significantly higher in the pre‐transplant NGS MRD‐positive (vs MRD‐negative) subjects (P = .014). After adjusting for TP53 mutation and transplant conditioning regimen, NGS MRD‐positivity retained independent prognostic significance for leukemic relapse (subdistribution hazard ratio = 7.3; P = .05). The pre‐transplant NGS MRD‐positive subjects also had significantly shortened progression‐free survival (P = .038), and marginally shortened overall survival (P = .068). In patients with AML undergoing HSCT, the pre‐transplant persistence of NGS‐defined MRD imparts a significant, sensitive, strong, and independent increased risk for subsequent leukemic relapse and death. Given that NGS can simultaneously detect multiple leukemia‐associated mutations, it can be used in the majority of AML patients to monitor disease burdens and inform treatment decisions.